Sustained discontinuation of infliximab with a raising-dose strategy after obtaining remission in patients with rheumatoid arthritis: the RRRR study, a randomised controlled trial. Issue 1 (19th October 2019) - Tanaka, Yoshiya; Oba, Koji; Koike, Takao; Miyasaka, Nobuyuki; Mimori, Tsuneyo; Takeuchi, Tsutomu; Hirata, Shintaro; Tanaka, Eiichi; Yasuoka, Hidekata; Kaneko, Yuko; Murakami, Kosaku; Koga, Tomohiro; et al.
Abstract : Objectives: The aim of this study is to determine whether the 'programmed' infliximab (IFX) treatment strategy (for which the dose of IFX was adjusted based on the baseline serum tumour necrosis factor α (TNF-α)) is beneficial to induction of clinical remission after 54 weeks and sustained discontinuation of IFX for 1 year. Methods: In this multicentre randomised trial, patients with IFX-naïve rheumatoid arthritis with inadequate response to methotrexate were randomised to two groups; patients in programmed treatment group received 3 mg/kg IFX until week 6 and after 14 weeks the dose of IFX was adjusted based on the baseline levels of serum TNF-α until week 54; patients in the standard treatment group received 3 mg/kg of IFX. Patients who achieved a simplified disease activity index (SDAI) ≤3.3 at week 54 discontinued IFX. The primary endpoint was the proportion of patients who sustained discontinuation of IFX at week 106. Results: A total of 337 patients were randomised. At week 54, 39.4% (67/170) in the programmed group and 32.3% (54/167) in the standard group attained remission (SDAI ≤3.3). At week 106, the 1-year sustained discontinuation rate was not significantly different between two groups; the programmed group 23.5% (40/170) and the standard group 21.6% (36/167), respectively (2.2% difference, 95% CI −6.6% to 11.0%; p=0.631). Baseline SDAI <26.0 was a statistically significant predictor of the successfully sustained discontinuation of IFX at week 106. Conclusion: Programmed treatment strategy did not statistically increase the sustained remission rate after 1 year discontinuation of IFX treatment.